2021
DOI: 10.36661/2595-4520.2021v4i5.12567
|View full text |Cite
|
Sign up to set email alerts
|

Análise das Questões do ENEM relativas aos Biomas Brasileiros no Período 2015-2019

Abstract: Este artigo é decorrente da pesquisa desenvolvida para a dissertação de mestrado da primeira autora e tem por objetivo analisar as questões da prova de Ciências da Natureza e suas Tecnologias, do Exame Nacional do Ensino Médio (ENEM), no período 2015-2019. Considerando-se a extensão do conteúdo, elegeu-se, para análise, as questões relativas aos biomas brasileiros da prova de Biologia e se constatou que, no período analisado, conhecimentos de Ecologia foram frequentes nas provas de Ciências da Natureza e suas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Over the last few decades, research in the area of Natural Sciences (Chemistry, Physics and Biology) has demonstrated concerns about the teaching offered in school spaces (Alves et al, 2021;Simplício et al, 2020) and the way in which the contents have been addressed in entrance exams in higher education (Hernandes;Martins, 2013;Schneider;Scheid;Boer, 2021). These studies reinforce the need to reflect and discuss teaching and learning processes that provide the opportunity for the development of "[...] thinking capabilities, in order to acquire knowledge to understand scientific debates, issues related to technology, and understanding the complex interactions involving Science and Society" (Teixeira, 2019, p. 851).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, research in the area of Natural Sciences (Chemistry, Physics and Biology) has demonstrated concerns about the teaching offered in school spaces (Alves et al, 2021;Simplício et al, 2020) and the way in which the contents have been addressed in entrance exams in higher education (Hernandes;Martins, 2013;Schneider;Scheid;Boer, 2021). These studies reinforce the need to reflect and discuss teaching and learning processes that provide the opportunity for the development of "[...] thinking capabilities, in order to acquire knowledge to understand scientific debates, issues related to technology, and understanding the complex interactions involving Science and Society" (Teixeira, 2019, p. 851).…”
Section: Introductionmentioning
confidence: 99%
“…Ao longo das últimas décadas, pesquisas na área de Ciências da Natureza (Química, Física e Biologia) têm demonstrado preocupações com o ensino ofertado nos espaços escolares (Alves et al, 2021;Simplício et al, 2020) e com a forma como os conteúdos vêm sendo abordados nos processos seletivos de ingresso no ensino superior (Hernandes;Martins, 2013;Schneider;Scheid;Boer, 2021). Esses estudos reforçam a necessidade de refletir e discutir processos de ensino e aprendizagem que oportunizem o desenvolvimento de "[...] capacidades de pensamento, no sentido de ocorrer uma aquisição do conhecimento para o entendimento de debates científicos, de questões ligadas à tecnologia, e de compreensão das interações complexas envolvendo Ciência e Sociedade" (Teixeira, 2019, p. 851).…”
Section: Introductionunclassified